Translator's voice in translating narrative space in Chinese children's fiction Bronze and Sunflower into English - Zhao, Meijuan (2023)
Translating narrative space is a necessity due to its fundamental role in children’s literature. Narrative space refers to the physical environment in which the characters of narrative live and move. However, there are scarce studies on how narrative space is translated and how the translator’s voice is perceived during this process. The current study thus seeks to explore the rendering of narrative space and to trace the translator’s voice in the English translation of narrative space in Chinese children’s fiction Bronze and Sunflower. The theoretical framework of this study is based on Ryan et al.’s (2016) model of narrative space, Baker’s (2006) framing strategies and E. O’Sullivan’s (2005) translator’s voice. The novelty of this study is in its focus on the translation of narrative space from the Chinese language to English. Methodologically, an interpretive qualitative approach was designed and a total of 1,581 samples were selected from Cao Wenxuan’s 青铜葵花 (2005) and Bronze and Sunflower (2017), the English translation of W. X. Cao’s work by Helen Wang. Qualitative content analysis was used and it was found that translation did alter the structure of narrative space in terms of omission, addition, permutation, and substitution. Furthermore, selective appropriation was the most frequently used framing strategy in rendering narrative space. It was evident that the translator preferred to omit some repeated spatial frames even though the source text elaborated on them many times. The translator’s preference consequently softened the sense of space in the target context, and that influenced readers’ reading experience. Moreover, it was observed that the translator’s voice was specifically loud in the way of reductive narration. The reason may be that the target text was only graded for readers aged 9-12, while the source text was classified into children’s literature without specific age limitations. These findings not only enhance the awareness of the translator’s visibility and creativity, they also extend the applicability of Baker’s framing strategies, which may provide new insights into a better understanding of spatial issues in the translation of children’s literature.